Enhance foreign body image using partitioned iterated function system (PIFS) in image enhancement technique / Hidayah Sharif - Sharif, Hidayah (2010)
This prototype was developed to enhance foreign body images using Partitioned Iterated Function System (PIFS). The study focuses on patient with suspected fish bone within the esophagus area from x-ray images. Sometimes radiographic images produced poor quality result. This prototype is about image enhancement that can be used by doctors to detect fish bone. At the same time, this application can be used for doctors to train medical students. This application used one of the image enhancement techniques which his Partitioned Iterated Function System (PIFS) algorithm. Through the development of the application, the effectiveness of the result has been evaluated. Noise image can be removed effectively with PIFS algorithm but the problem is high computational complexity in the searching process.